The Impact Of Bitcoin On Indonesian Banking: Opportunities And Challenges - Setiyo Purwanto; Nur Endah Retno Wuryandari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study explores the impact of Bitcoin on the Indonesian banking sector, emphasizing both the innovative opportunities and the challenges it presents. The research highlights Bitcoin's potential to enhance financial inclusion and drive technological growth while also identifying significant hurdles such as regulatory issues, security risks, and market volatility. Utilizing a mixed-methods approach, the study provides a nuanced analysis of Bitcoin's dual role as both a beneficial and threatening force within the financial landscape. It categorizes research variables into dependent, independent, and control groups to better understand their interactions and influence on traditional banking systems. The paper identifies a critical gap in existing literature regarding Bitcoin's specific effects on Indonesian banking operations, offering an empirical foundation for future research. The findings underscore the evolving regulatory frameworks and Bitcoin's complex role in the banking sector, highlighting the need for strategic management and careful regulation to harness its potential benefits while mitigating associated risks.